Energy–exergy analysis and mathematical modeling of cassava starch drying using a hybrid solar dryer. Issue 1 (1st January 2020) - Suherman, Suherman; Susanto, Evan Eduard; Zardani, Asif Widodo; Dewi, Nur Haniza Roviqoh; Hadiyanto, H.
Abstract: In this study, we aimed to energetically and exergetically evaluate the usage of a hybrid solar dryer system for cassava drying via a series of drying experiments. The experiments were performed beginning at 10.00 A.M. (hereafter, in local time) until the moisture content of cassava starch became constant at a value less than 14% on a wet basis at drying temperatures of 40 °C to 60 °C and drying times of 180–240 min. The results demonstrated that the highest overall dryer energetic efficiency was 20.82%, which was achieved at a drying temperature at 60 °C, and that the maximum energetic efficiency of 27% was recorded at 11.00 A.M. The exergy flows fluctuated during the drying process and were dependent on the solar radiation and drying conditions; however, the exergetic efficiency of the dryer was 25.1%–73.8%. Comparison of the fitting models denoted that the Page model was the most suitable model for describing the experimental drying performances. The calculated effective diffusivity constant ( Deff ) and the activation energy ( Ea ) during the drying process from 50 °C to 60 °C were 3·× 10 −10 m 2 /s and 15.3 kJ/mole, respectively.